Using The Value of GPS To Determined The Position Of The Mobile User in Mosul University - Ghaydaa Al-Talib; Hiba Yahya (Al-Rafidain Journal of Computer Sciences and Mathematics)
The Mobile is a circuit that  receives and sends signals through earth stations and satellites so the objective of this research is to build a system that retrieves information about  the location of the  mobile user . The proposed system gets information of the location of the mobile user within Mosul university depending on the values of longitude and Latitude that have  been received from GPS . The system displays on the mobile screen the values of longitude and latitude of the current location, as well as a list of names for the nearest buildings that surrounding the user location . The system works on a mobile model (Nokia) from the third generation and beyond. This mobile has an integrated GPS receiver. The job of this receiver is to receive the incoming signals from the satellites, and they are  working out of the buildings (out door). We used the Java 2 Micro Edition   (J2ME) Language to write the program for this application, since it is the language that is mostly used to write the mobile applications.